Balancing Fluency and Accuracy Practices: Model of Instruction from a Private English Course - Rahma Pitria Ningsih (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2020)
This observational research focused on the teaching methods to investigate the techniques and strategies employed by the English instructors in their teaching-learning in the classroom. The present study analyzed the findings and figured out the useful model of instruction, which can cover both accuracy and fluency practices. A descriptive qualitative approach was the design of the research by utilizing observation and interviews as data collection methods. The observation was conducted to record the practice of teaching for ten meetings. During the observation, field notes and observation checklist were used to carefully collect all the data needed during the teaching and learning process. Eight English instructors at the course were invited for interviews so more comprehensive data related to their method and teaching strategies can be gathered. The findings of the research showed that ELITE English Course Banjarmasin applied the combination of Communicative Language Teaching (CLT) and Presentation Practice Production (PPP) as a model of their instructions, so the students got opportunities to practice both accuracy and Fluency in the classroom. During the observation, field notes and observation checklist were used to carefully collect all the data needed during the teaching and learning process.